2015
DOI: 10.14737/journal.aavs/2015/3.3.151.155
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Prevalence and Gross Pathology of Liver Fluke Infestation in Sheep in and Around Quetta District, Pakistan

Abstract: | The study was conducted to determine the prevalence of fascioliasis in sheep in Quetta district from January to June 2007. Two hundred and fifty liver samples along with gall bladder and bile ducts were collected from sheep. Over all prevalence of liver fluke infestation in sheep was recorded as 30% in young and adult and 32% in aged sheep. Out of these positive samples Fasciola hepatica was found 50% and Fasciola gigantica 10% in case of young whereas in adults 20% with fasciola hepatica and 14%with Fasciol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
1
10
1
Order By: Relevance
“…This result was in contradiction with the findings (Dhakal, and Nepali, 1984) and (Sardar, et al, 2016) who found adult more susceptible to infestation. Young animals are more susceptible to parasitic infection than adult (Khan et al, 2017). This higher infestation of parasite in the young can be due the inadequate immunity against the parasite than that of the adult.…”
Section: Resultsmentioning
confidence: 99%
“…This result was in contradiction with the findings (Dhakal, and Nepali, 1984) and (Sardar, et al, 2016) who found adult more susceptible to infestation. Young animals are more susceptible to parasitic infection than adult (Khan et al, 2017). This higher infestation of parasite in the young can be due the inadequate immunity against the parasite than that of the adult.…”
Section: Resultsmentioning
confidence: 99%
“…In general, pathology of the disease is similar in sheep and goats. In sheep common lesions of livers were variable degree of cholangitis, biliary obstruction, fibrosis, hyperplasia, hemorrhages, enlargement, fibrinous exudation and oedema (Khan et al, 2015). In goats, affected livers were enlarged with hemorrhagic spots, hepatic bile duct protruding and engorged (Islam et al, 2016).…”
Section: Trematodes Infectionsmentioning
confidence: 99%
“…In the present study, degenerative changes comprised of hepatic cell swelling (23.81%), hydropic degeneration (18.09%), fatty changes (8.57%) and coagulative necrosis (18.09%). Khan et al, (2015) recorded a higher occurrence of hepatic cell swelling with 52.63 per cent. Hassanein et al, (2017) recorded a lower occurrence of hydropic degeneration at 0.002 per cent.…”
Section: Degenerative and Necrotic Changesmentioning
confidence: 92%
“…In the present study, circulatory disturbances in liver comprised of congestion (73.33%), haemorrhages (21.90%) and thrombosis (0.95%). Bhavyapriyanka (2017) recorded a lower occurrence of 2.24 per cent of congestion whereas Khan et al, (2015) recorded a higher occurrence of 47.36 per cent of haemorrhages. Congestion was found to occur frequently in sheep belonging to nomadic herds which could be attributed exposure to various toxic agents through ingestion of environmental toxicants or plants during migratory period.…”
Section: Circulatory Disturbancesmentioning
confidence: 97%